The contribution of eutectic liquid film to the TMAZ microfissuring in intertia friction welded PM RR1000 superalloy (2010)
The microstructure of the base alloy and thermomechanical affected zone (TMAZ) of inertia friction welded powder metallurgy (PM) RR1000 were examined by the use of standard metallogrphic techniques involving optical, analytical scanning transmission electron microscopes equipped with energy dispersive spectometer and an electron probe micro analyser. It was discovered that liquation of grain boundary phases present in the pre-weld alloy resulted in the formation of eutectic type ƴ-ƴ1 solute rich liquid film predominant in the TMAZ regions whic contributed significantly to micro fissuring during welding. It was found that apart from the effect of rapid precipitation of ƴ particles on the TMAZ cracking as has been widely reported, constitutinal liquidation of ƴ particles was a notable part of liquidation process which promoted the susceptibility of TMAZ to microcracking.